2012
DOI: 10.5902/198050987561
|View full text |Cite
|
Sign up to set email alerts
|

Influência das características anatômicas e do teor de extrativos totais da madeira de <i>Eucalyptus grandis</i> W. Hill ex Maiden na qualidade da colagem

Abstract: RESUMOO trabalho teve como objetivo caracterizar anatomicamente e quantificar os extrativos totais em diferentes posições de toras de Eucalyptus grandis W. Hill ex Maiden com 18 anos de idade e avaliar a influência dessas características sobre a resistência ao cisalhamento e percentagem de falhas na madeira de juntas coladas com adesivo termoendurecedor resorcinol-formaldeído. Foram preparadas lâminas histológicas para o estudo anatômico e determinou-se o teor de extrativos totais. A preparação das juntas cola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
13
0
4
Order By: Relevance
“…The greater the fiber diameter and ray width, the greater the adhesive penetration in the cells, and consequently the greater the adhesion between the wood pieces and the shear strength in the glue line (Albino et al, 2012). However, this fact was not observed for Kiri wood, which exhibited the lowest shear strength.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The greater the fiber diameter and ray width, the greater the adhesive penetration in the cells, and consequently the greater the adhesion between the wood pieces and the shear strength in the glue line (Albino et al, 2012). However, this fact was not observed for Kiri wood, which exhibited the lowest shear strength.…”
Section: Resultsmentioning
confidence: 96%
“…The type of adhesive to be used during the adhesion process should also be considered. For example, resorcinol formaldehyde is a widely used adhesive in structural parts because it gives bonded joints, resistance against mechanical stress, moisture and temperature, despite its high cost (Tienne et al, 2011;Albino et al, 2012). A strategy to reduce costs is the use of resorcinol in wood species with different anatomical structures, which provides an accurate diagnosis to adjust its behavior in the bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to results obtained by Albino, Mori and Mendes (2012), when pore diameter dimension, the width and the fiber length and ray width are too high, they might result in a thick glue line since more adhesive is absorbed.…”
Section: Bonding Qualitymentioning
confidence: 99%
“…In evaluating the influence of the anatomical characteristics and the total extractive content in Eucalyptus grandis wood on the quality of the bonding, Albino et al (2012) showed that the extractive content in the region of the pith and on top of the log were 6.10% and 7.98%, respectively. Loiola (2015) analyzed the drying of teak wood (Tectona grandis L. f) and found total extractive values of 11.13%.…”
Section: Physical and Chemical Wood Propertiesmentioning
confidence: 99%